Fibrinogen beta variants confer protection against coronary artery disease in a Greek case-control study - Zakopoulos Nikolaos; Richter Dimitrios; Papamikos Vassileios; Kolovou Genovefa; Fili Panagiota; Peppes Vassileios; Suhorutšenko Julia; Nikopensius Tiit; Theodoraki Eirini V; Krjutškov Kaarel; Metspalu Andres; Dedoussis George V (BMC, 2010)
Abstract Background Although plasma fibrinogen levels are related to cardiovascular risk, data regarding the role of fibrinogen genetic variation in myocardial infarction (MI) or coronary artery disease (CAD) etiology remain inconsistent. The purpose of the present study was to investigate the effect of fibrinogen A (FGA), fibrinogen B (FGB) and fibrinogen G (FGG) gene SNPs and haplotypes on susceptibility to CAD in a homogeneous Greek population. Methods We genotyped for rs2070022, rs2070016, rs2070006 in FGA gene, the rs7673587, rs1800789, rs1800790, rs1800788, rs1800787, rs4681 and rs4220 in FGB gene and for the rs1118823, rs1800792 and rs2066865 SNPs in FGG gene applying an arrayed primer extension-based genotyping method (APEX-2) in a sample of CAD patients (n = 305) and controls (n = 305). Logistic regression analysis was used to calculate odds ratios (ORs) and 95% confidence intervals (CIs), before and after adjustment for potential confounders. Results None of the FGA and FGG SNPs and FGA, FGB, FGG and FGA-FGG haplotypes was associated with disease occurrence after adjustment. Nevertheless, rs1800787 and rs1800789 SNPs in FGB gene seem to decrease the risk of CAD, even after adjustment for potential confounders (OR = 0.42, 95%CI: 0.19-0.90, p = 0.026 and OR = 0.44, 95%CI:0.21-0.94, p = 0.039, respectively). Conclusions FGA and FGG SNPs as well as FGA, FGB, FGG and FGA-FGG haplotypes do not seem to be important contributors to CAD occurrence in our sample. On the contrary, FGB rs1800787 and rs1800789 SNPs seem to confer protection to disease onset lowering the risk by about 50% in homozygotes for the minor alleles.